1996
DOI: 10.1074/jbc.271.51.32491
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of a Novel KRAS Insertion Mutation from a Human Leukemia

Abstract: A novel alteration in exon 1 of KRAS was detected by single strand conformational polymorphism analysis of DNA amplified from the bone marrow of a 4-year-old child with myeloid leukemia. Sequencing of this mutant allele revealed an insertion of three nucleotides between codons 10 and 11 resulting in an in-frame insertion of glycine. Expression of the mutant protein in NIH 3T3 cells caused cellular transformation, and expression in COS cells activated the Ras-mitogen-activated protein kinase signaling pathway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 24 publications
7
41
0
Order By: Relevance
“…S5 A). Similar molecular alterations had been previously found in animal and human tumors (26,27). Biochemical analysis demonstrated that this insertion strongly activates KRAS by permanently switching the corresponding mutated protein into the GTP-bound active state (Fig.…”
Section: Knock-in Cells Display Drug Responses Resembling Those Of Tusupporting
confidence: 57%
“…S5 A). Similar molecular alterations had been previously found in animal and human tumors (26,27). Biochemical analysis demonstrated that this insertion strongly activates KRAS by permanently switching the corresponding mutated protein into the GTP-bound active state (Fig.…”
Section: Knock-in Cells Display Drug Responses Resembling Those Of Tusupporting
confidence: 57%
“…Multiple studies have shown that alterations across KRAS exons 2, 3, and 4 similarly predict cetuximab and panitumumab resistance, and the National Comprehensive Cancer Network (NCCN) and American Society for Clinical Oncology (ASCO) guidelines have expanded to recommend extended KRAS testing, as well as testing for NRAS and BRAF mutations [6,9,15,16,52]. Additionally, KRAS insertions within or adjacent to hotspot regions have been reported; these mutations have been characterized as activating and oncogenic, and may similarly predict resistance, although this has not yet been established [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Translocations involving this region were also shown to be important for ALL leukemogenesis [44][45][46]. Similarly, KRAS2 protein with a genetic insertion was shown to play a role in malignant transformation by activating the RAS-activated signaling pathway in acute myeloid leukemia (AML) cells [47]. Additionally, some cases of AML were caused by alterations in CEBPA and NPM proteins via mutations [48,49].…”
Section: Exploitation Of Protein Profiling In Leukemia Researchmentioning
confidence: 99%